PRELIMINARY PHYTOCHEMICAL ANALYSIS AND GAS CHROMATOGRAPHY MASS SPECTROMETRY SPECTRA OF CHLOROFORM EXTRACT FROM SPERMACOSE HISPIDA L. SEED - Anantharaman, Gokula Krishnan; Krishnamoorthy, Gayathri (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: Globally, scientific evaluation of traditional uses of herbal medicine, isolation, and characterization of bioactive constituents from herbs are some of the leading research areas. Spermacoce hispida (SH) is well known for its hypolipidemic and anti-obesity activity. The aim of this study is to qualitatively analyze the presence of primary and secondary metabolites in various extracts of SH seeds and to examine the presence of bioactive principles of chloroform extract from SH seeds. Methods: Physicochemical analysis such as ash content, acid-soluble ash, water-soluble ash, moisture content, fiber content, ethanol soluble extractive value, and water-soluble extractive value for seeds of SH was determined as per WHO guidelines. Cold percolative extracts of seeds of SH with different solvents were carried out. Preliminary phytochemical analysis for the presence of various primary and secondary metabolites in extracts was determined. Gas chromatography mass spectrometry (GC-MS) analysis of chloroform extract was carried out. Results: Physicochemical analysis values were found to be present in permissible level (<5%). Yield of ethyl acetate (4.9/100 g), ethanolic (4.2/100 g), and hydroalcoholic extract (4.0/100 g) of seeds of SH was found to be higher than that of extract obtained by soaking with different low polar solvents. Secondary metabolites such as phenol, flavonoid, and tannin are present in ethyl acetate, ethanolic, hydroalcoholic extract. Fat and alkaloid are present in chloroform extract. GC-MS spectra show the presence of 30 different bioactive constituents. Among them, n-hexadecanoic acid was found to constitute (5.83%) highest peak area than the remaining compounds. Conclusion: Seeds of SH is a rich source of primary and secondary metabolites and various bioactive phytoconstituents.